Las relativas sin antecedente en los siglos XVIII y XIX: Variación y contextos de uso - Vellón Lahoz, Francisco Javier (El Colegio de México, A.C., 2020)
This paper examines the alternation of the pronouns quien/el que in relative clauses without a human-referring antecedent in the 18th and 19th centuries. Based on a corpus of ‘language of immediacy’ (mainly private letters, but also diaries and memoirs), and using a variationist methodology, the study analyzes the linguistic and sociolinguistic factors that favor the survival of the constructions with quien as against the dominant use of el que. The research shows that, in the face of the advance of the clauses headed by el que, there are contexts in which the variant quien is very firm, which explains its gradual recovery from the second half of the 19th century.